Use Wh Questions In Nursing Services As An Effort To Prepare Competitive Nurses In The Nursing Study Program Of Timor University - Sefrina Maria Seuk Asa (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Mastery of English for Nursing has become an important trend in nursing education in response to the increasing demand for competitive nursing professionals in the era of globalization. One essential basic competence is the use of WH questions in nursing communication to obtain patient data and information. This study employed a qualitative method using interviews, observation, and literature review. Interviews were conducted with 30 third-year nursing students of the University of Timor who had completed clinical practice in hospitals and community health centers. The results indicate that the appropriate use of WH questions (what, who, when, where, why, and how) helps nurses establish effective communication, obtain accurate information regarding patients’ conditions and medical histories, and support decision-making in nursing care. In conclusion, mastery of WH questions is a crucial component of English for Nursing learning in preparing professional and competitive nursing personnel.